Compositional quality of the silage of three cultivars of corn (Zea mays) from the Colombian high tropics - Mancipe-Muñoz, Edgar A. (2022)
Introduction. The elaboration of high-quality corn-silage is a strategy to improve the efficiency of ruminant feeding systems. Objective. To evaluate the effect of cob proportion and sealing time on the compositional quality of silage of three maize cultivars in the Colombian high tropic, harvested in the reproductive phase of milky-pasty grain. Materials and methods. The experiment was conducted in 2017 in Mosquera, Colombia, with the cultivars Simijaca, Medellín, and Pionner. Experiment 1, four different proportions of cob were generated in the silage. Experiment 2, the biomass was ensiled at 0, 8 or 16 hours of wilted. Dry matter (DM), crude protein (CP), starch, and neutral detergent (NDF) and acid detergent (ADF) fibers were determined. The dynamic of pH decrease was evaluated. The effect of cob proportion and wilting time on the DM, OM, and NDF digestibility was determined only in the Simijaca cultivar. Compositional quality and pH dynamics were analyzed using a completely randomized design with a factorial arrangement, while digestibility was analyzed using a completely randomized design. Results. The Medellín cultivar showed lower cob proportion and starch concentration (11.9 %) (p<0.05) and a higher NDF content (51.7 %) (p<0.05). Greater cob content increased starch concentration, energy, and digestibility (p<0.05), and reduced (p<0.05) the final pH value (3.69). Wilted time increased DM, NDF (p<0.05) and final pH value and rate of pH decline, but did not change DM, OM, and NDF digestibility. Conclusion. Using corn silage with more than 66% of cob and rapidly sealing the biomass of the Simijaca and Pioneer cultivars improved the fermentation conditions and compositional quality.